Produtividade e qualidade de sementes de feijão-vagem produzidas sob sistemas convencional e orgânico - Portal, Ruanny Karen Vidal Pantoja (2017)
Over the last few years, environmental aspects have been focused, requiring to develop and produce in a sustainable way. In this way, the need arises for an alternative production that is in opposition to the current model. Organic agriculture comes as an alternative to the current model, because in this production system the use of substances that cause direct impacts to human health and the environment is not allowed. Brazil is one of the countries with the greatest potential for growth and development of organic agriculture. The production of organic seeds is already carried out in Brazil, but in a reduced quantity and through conventional seeds due to the lack of organic seeds in quantity and quality in the market. The use of quality seeds is the factor that, in isolation, contributes most to obtaining high grain yields in the bean crop. Snap beans are considered one of the world's top vegetables, with a production of 6.5 million tons per year. In Brazil, it is among the ten most produced vegetables, its growth habit is one of the most important characteristics for classification, as it is essential both in the description of cultivars and in the choice of cultivars for different cultivation systems. It can be classified as: undetermined or determined. However, its production for human consumption is characterized largely by cultivars with an indeterminate growth habit, on average its national productivity is 2,000 kg / ha. However, in order to achieve maximum productivity efficiency, it is necessary to use good quality seeds. This quality refers to the sum of all the genetic, physical, physiological and health attributes that influence the ability to originate plants with high productive potential. Another important factor that can influence productivity and physiological quality is the soil management system. It is fundamental to analyze and characterize the physiological potential of the seeds produced in different management practices. In this sense, the objective of this study was to evaluate new snap bean strains, with indeterminate growth, regarding the production and quality of seeds produced under conventional and organic systems, in relation to the main cultivars in the Brazilian market. For this, two field trials were carries out at EMATER-Goiás, in which the development and yield of 20 genotypes of snap beans were evaluated in the conventional and organic production systems in the period of August / 2016. Based on field evaluations, the UEG 0212, UEG 2014 and UEG 3014 lines showed good performance in both production systems, thus being suitable for planting in both systems. After completing the field experiment, physiological quality evaluations of the seeds from the first experiments were carried out, and the quality tests were performed at UEG, Câmpus Ipameri. After the tests, it was concluded that the production systems influenced the physiological quality of the bean seeds, the cultivar Macarrão Bragança and the lineages UEG 0412, UEG 0812, UEG 0912, UEG 1312, UEG 0914 and UEG 2514 presented seeds with high performances in the organic production system